Incidence and risk factors of suicide among patients with pancreatic cancer: A population-based analysis from 2000 to 2018 - Ma, Yifei; Lyu, Jun; Yang, Bao; Yan, Tianao; Ma, Qingyong; Wu, Zheng; Wang, Zheng; He, Hairong (Frontiers in Oncology, 2022)
Background: The rate of suicide within one year after diagnosis in pancreatic cancer patients are high, but suicide studies based on the current large-scale data are still a vacancy. Our study aimed to determine, compared to the general population, the standardized mortality ratios (SMRs) of suicide and risk factors associated with pancreatic cancer patients committing suicide to provide clues for prevention. Methods: We collected 199,604 patients diagnosed with pancreatic cancer between 2000 and 2018 from the SEER database. Multivariate logistic regression and multivariate Cox regression were applied to determine the risk factors independently affecting the suicide outcome of pancreatic cancer patients. Results: A total of 180 suicide deaths were observed in the cohort, yielding an overall suicide rate of 88.05 per 100,000 person-years and an SMR of 6.43. In multivariate analyses, males (HR: 12.798, 95% CI: 7.471-21.923), unmarried (HR: 1.826, 95% CI: 1.205-2.767), and divorced, separated or widowed (HR: 1.779, 95% CI: 1.230-2.572) were found associated with a higher risk of suicide. While race black (HR: 0.250, 95% CI: 0.110-0.567), diagnosed with pancreatic neuroendocrine tumor (HR: 0.487, 95% CI: 0.276-0.859), received chemotherapy (HR: 0.456, 95% CI: 0.323-0.646), and received surgical procedures (HR: 0.553, 95% CI: 0.342-0.895) were indicated might protective factors. Conclusions: The 199,604 pancreatic cancer patients diagnosed between 2000 and 2018 had an overall suicide rate of 88.05 per 100,000 person-years and an SMR of 6.43 compared to the U.S. general population. Male, white, unmarried, and diagnosed with pancreatic adenocarcinoma patients were associated with a higher risk of suicide, while cancer-directed surgery and chemotherapy might indicate protective factors. The screening and prevention process should be enhanced for pancreatic cancer patients with adverse risk factors. Moreover, it is reasonable to assume that timely cancer-directed treatment might help reduce the subsequent suicide risk of pancreatic cancer patients.